1945
DOI: 10.1021/ja01217a016
|View full text |Cite
|
Sign up to set email alerts
|

Lead Tetraacetate Oxidation of Aminoalcohols

Abstract: Lead Tetraacetate Oxidation of Aminoalcohols 49 tíllate showed that the product corresponded roughly to heptaallyl sucrose: m20d 1.4912; d20, 1.1071; viscosity at 25°, 792.5 centipoises; [a]MD +50.5°; molecular refraction, 163.01 (caled, for heptaallyl sucrose, 164.79); allyl, 44.3% (caled, for C33H50O11, 46.2%).Acknowledgment.-The assistance of Esther M. Terry, who made the free-hydroxyl and unsaturation determinations, and of A. N. Wrigley, who helped to prepare some of the compounds, is gratefully acknowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1948
1948
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Nicolet and Shinn had observed that N-diethylaminoethanol, a tertiary hydroxyamine, was not affected by periodic acid (8). Later Leonard and Rebenstorf confirmed the same observation under more strenuous conditions (9). Using a procedure recommended by Siggia (10), we found that diol III consumed about two moles of periodic acid.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Nicolet and Shinn had observed that N-diethylaminoethanol, a tertiary hydroxyamine, was not affected by periodic acid (8). Later Leonard and Rebenstorf confirmed the same observation under more strenuous conditions (9). Using a procedure recommended by Siggia (10), we found that diol III consumed about two moles of periodic acid.…”
supporting
confidence: 71%
“…Later Leonard and Rebenstorf confirmed the same observation under more strenuous conditions (9). Later Leonard and Rebenstorf confirmed the same observation under more strenuous conditions (9).…”
Section: Kwan-chung Tsou Andsupporting
confidence: 57%
“…The bridgehead aminium radical derived from 1-azaadamantane 23 which is isoelectronic with 14+• as well as the even more strained species from 1-azabicyclo[2.2.2]octane (22) and 1-azabicyclo[2.2.1]heptane (21) have been reported. 173 The 23+• respectively, which compared with aN = 20.7 G for the trimethylaminium radical.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…The majority of these methods involve cleavage of a C−H bond at the α-position of an amine substrate [ 7 28 ]. Methods that deliver imines through amine α-C−C bond cleavage are far less common [ 29 32 ] despite the fact that these methods employ renewable resources, such as amino acids and their derivatives, as starting materials. In fact, only a few reports describing the oxidative deformylation of amino alcohols have been published [ 33 35 ], and in all of these reports stoichiometric oxidants, such as NaIO 4 and Pb(OAc) 4 , must be employed to enable the desired transformations.…”
Section: Introductionmentioning
confidence: 99%